Implementasi Customer Relationship Management (CRM) Pada Penerimaan Siswa Baru (Studi Kasus di Pondok Pesantren Darussalam Kabupaten Garut) - Jajang Abdurahman; Dadang Hamdani; Panji Novantara (FKOM UNIKU, 2018)
Along the tight competition in education field, especially the recruitment of students, the school manager faces problem in making right decision. In addition, to maintain the potential learners, it also needs an effort to get new learners through best strategies of school promotion. Therefore, improving service quality to win promotion competition is very important to do.One of methods in improving service towards customer is customer relationship management (CRM), as a comprehensive business strategy of a company that enables the enterprise to manage customer relationships effectively, in this research, the writer uses Operational Customer Relationship Management. Whereas the method of system development used is Waterfall method.The system is built as a base Web to expand the spread of online new student enrollment information, so this programme is potentially to get new learners, the system was built as a web based, it uses PHP programming language and MySQL as data storage media and SMS Gateway as a support system in facilitating the students’ and parents’services, testing methods also used black box white box testing. This system can be used by 4 access, they are students, parents, New Students enrollment committee and head devision of TMI.Using computer technology, Customer Relationship Management (CRM) is more developed and wider system because using CRM can keep the customers of the existing learners, the recruitment of new learners, the faster responses to learners’ parents, and so on.Keywords: Online New Student Registration, Customer Relationship Management (CRM) Operational, Waterfall, Web